Adverse Childhood Experiences and Telomere Length a Look Into the Heterogeneity of Findings—A Narrative Review - Bürgin, David; O'Donovan, Aoife; d'Huart, Delfine; di Gallo, Alain; Eckert, Anne; Fegert, Jörg; Schmeck, Klaus; Schmid, Marc; Boonmann, Cyril (Frontiers in Neuroscience, 2019)
Background: Adverse childhood experiences (ACEs) have been associated with poor mental and somatic health. Accumulating evidence indicates that accelerated biological aging – indexed by altered telomere-related markers – may contribute to associations between ACEs and negative long-term health outcomes. Telomeres are repeated, non-coding deoxyribonucleic acid (DNA) sequences at the end of chromosomes. Telomeres shorten during repeated cell divisions over time and are being used as a marker of biological aging. Objectives: The aim of the current paper is to review the literature on the relationship between ACEs and telomere length (TL), with a specific focus on how the heterogeneity of sample and ACEs characteristics lead to varying associations between ACEs and TL. Methods: Multiple databases were searched for relevant English peer-reviewed articles. Thirty-eight papers were found to be eligible for inclusion in the current review. Results: Overall, the studies indicated a negative association between ACEs and TL, although many papers presented mixed findings and about a quarter of eligible studies found no association. Studies with smaller sample sizes more often reported significant associations than studies with larger samples. Also, studies reporting on non-clinical and younger samples more often found associations between ACEs and TL compared to studies with clinical and older samples. Reviewing the included studies based on the ‘Stressor Exposure Characteristics’ recently proposed by Epel and colleagues (2018) revealed a lack of detailed information regarding ACEs characteristics in many studies. Conclusion: Overall, it is difficult to achieve firm conclusions about associations of ACEs with TL due to the heterogeneity of study and ACE characteristics and the heterogeneity in reported findings. The field would benefit from more detailed descriptions of study samples and measurement of ACEs.